2016
DOI: 10.1007/s13555-016-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturation of Calcipotriene and Betamethasone Dipropionate in a Novel Aerosol Foam Formulation for Topical Treatment of Psoriasis Provides Enhanced Bioavailability of the Active Ingredients

Abstract: IntroductionPrevious studies have demonstrated the superior efficacy of a novel aerosol foam formulation of fixed combination calcipotriene 0.005% (Cal) and betamethasone dipropionate 0.064% (BD), compared with the ointment formulation. The aim of this study is to ascertain whether enhanced bioavailability of the active ingredients due to supersaturation and/or occlusive properties can explain the observed greater clinical efficacy.MethodsSolubility and evaporation experiments were conducted to examine the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 25 publications
2
64
1
2
Order By: Relevance
“…In most patients' samples, plasma concentrations of calcipotriol and betamethasone dipropionate and its metabolites were below the quantification's lower limit. 26,27 These results are consistent with those of tissue distribution's studies in rats administered with radiolabelled calcipotriol and betamethasone dipropionate, that showed that the kidney and liver had the highest radioactivity level. 27 In vitro skin penetration and ex vivo biomarker assays were conducted to compare the skin penetration and bioavailability of Cal and BD from the aerosol foam and ointment formulations, respectively.…”
Section: Pharmacokinetic Propertiessupporting
confidence: 86%
See 3 more Smart Citations
“…In most patients' samples, plasma concentrations of calcipotriol and betamethasone dipropionate and its metabolites were below the quantification's lower limit. 26,27 These results are consistent with those of tissue distribution's studies in rats administered with radiolabelled calcipotriol and betamethasone dipropionate, that showed that the kidney and liver had the highest radioactivity level. 27 In vitro skin penetration and ex vivo biomarker assays were conducted to compare the skin penetration and bioavailability of Cal and BD from the aerosol foam and ointment formulations, respectively.…”
Section: Pharmacokinetic Propertiessupporting
confidence: 86%
“…22 Cal/BD aerosol foam should be applied topically to the affected areas once daily for a maximum of 4 weeks, not exceeding 15 g daily or 60g every 4 days. 26,27,23 Clinical and pharmacological effects of the two active agents are well known, and its action mechanism in plaque psoriasis has been approached by several authors. 2,3,26 Treatment goal is to clear the psoriatic plaques by inhibiting the underlying inflammation and normalizing skin homeostasis, keratinocyte proliferation and differentiation, and to provide immunomodulation.…”
Section: State Of the Art On Psoriasis Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate-limiting step for most topical treatments is the concentration of active ingredients dissolved in the vehicle One potential method of enhancing the rate of skin penetration is to increase the concentration of active ingredients dissolved in the applied product beyond the normal solubility limit, ie create a supersaturated solution A recent study with Cal/BD aerosol foam demonstrated that a stable supersaturated environment was created and maintained for clinically relevant time periods (at least 26 hours in the laboratory setting) 21 -This state was created after rapid evaporation of the propellants during application and may explain the observed increase in bioavailability of Cal/BD aerosol foam versus Cal/BD ointment 21…”
Section: Challenges Of Drug Delivery In Topical Formulationsmentioning
confidence: 99%